Preparation method of vanadium-titanium pellets
By forming the internal and external structure of the pellets through two spheres, the blast furnace gravity ash is used to form pore channels, which solves the problem of uneven oxidation of vanadium titanium magnetite, improves the compressive strength and iron smelting efficiency of the pellet ore, and reduces transportation Costs improve corporate competitiveness.
Patent Information
- Application Number
- CN202411348530.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
During the process of ferrying vanadium titanium magnetite, the TFe grade and the TiO2 content of the blast furnace are low, resulting in uneven oxidation and a concentric crack structure, which reduces the compressive strength of the pelletized ore, and requires purchase of high-grade iron concentrate. Increase transportation costs and reduce corporate competitiveness.
Two sphere making methods are used to form different material structures inside and outside the pellet. The externally equipped with blast furnace gravity ash is burned to form pore channels during the preheating process, which promotes uniform oxidation and crystallization, improves the pellet ore pressure resistance. strength.
By forming good pore channels and uniform oxidation, the compressive strength of vanadium titanium pellets is improved, the blast furnace raw material conditions are stabilized, transportation costs are reduced, and iron smelting efficiency and enterprise competitiveness are improved.
Smart Images

Figure BDA0005061663840000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of iron and steel metallurgy, and in particular relates to a method for preparing vanadium-titanium pellets. Background Art
[0002] In order to improve the comprehensive utilization efficiency of vanadium-titanium magnetite in Panxi area of my country, Panzhihua Iron and Steel, as a world-renowned high-titanium vanadium-titanium magnetite ironmaking enterprise, has long been committed to improving the TFe grade of its own iron concentrate to reduce ironmaking costs. In the past decade, due to the limitations of ore properties and equipment, the TFe grade of Midea iron concentrate has been maintained at 53.5%, and the TFe grade of Baima iron concentrate has been maintained at 55%-56%, which is much lower than the TFe grade of ordinary iron concentrate (63%-67%). During blast furnace ironmaking, due to the Si / Ca ratio requirements of the sintering process, the vanadium-titanium iron concentrate has a low TFe grade and a high TiO2 content. In order to balance the furnace grade and the slag TiO2 content and ensure the smooth operation of the blast furnace, a large amount of high-priced high-grade iron concentrate is added during the ore blending process, resulting in a long-term stability of the TFe grade of the vanadium-titanium ore entering the blast furnace at 50.5% to 51.5% (57% to 58% for ordinary blast furnaces), and a ton of iron fuel ratio of up to 540 to 570 kg (470 to 480 kg for ordinary blast furnaces), which is much higher than the level of ironmaking using ordinary iron ore. In addition, the main ironmaking plants of Panzhihua Iron and Steel are located in the hinterland, and the transportation cost of the purchased external high-quality ores and fuels that can improve the technical and economic indicators of smelting is close to 200 yuan / t. The product sales market is far away from the production base, and the transportation cost is further increased, making the overall competitiveness of the enterprise lower than the advanced level of the industry.
[0003] The experience of blast furnace ironmaking production shows that if the TFe grade of the blast furnace is increased by 1%, the fuel ratio can be reduced by 2%, and the blast furnace utilization coefficient can be increased by 3%. If the TFe grade of vanadium-titanium iron concentrate is increased by 1%, the TFe grade of the blast furnace can be increased by 0.4-0.6 percentage points. To this end, Panzhihua Iron and Steel has carried out research on mineral processing technology, and the TFe grade of Midi vanadium-titanium concentrate has been increased to 55.5%, and the TFe grade of Baima vanadium-titanium concentrate has been increased to more than 57%. However, with the increase of TFe grade, the particle size of vanadium-titanium concentrate has been greatly refined. After the refined vanadium-titanium concentrate enters the pellet, during the preheating process, the Fe3O4 outside the pellet is rapidly oxidized to form a relatively dense Fe2O3 oxidation shell, which hinders oxygen from entering the pellet, resulting in poor preheating oxidation effect. The Fe3O4 inside the pellet can only be fully oxidized in the roasting stage, resulting in uneven oxidation time and oxidation degree, forming a concentric crack structure, which greatly reduces the compressive strength of the vanadium-titanium pellet. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for preparing vanadium-titanium pellets, which can ensure that the pellets produced from fine-grained high-titanium vanadium-titanium magnetite can form good pore channels during preheating and roasting, ensure uniform oxidation during preheating and roasting, improve the compressive strength of the pellets, stabilize the blast furnace raw material conditions, and strengthen blast furnace smelting.
[0005] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps:
[0006] a) pelletizing the first mixed material to obtain a green ball core; and then coating the surface of the green ball core with the second mixed material to obtain a green ball;
[0007] The first mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate and bentonite, and the second mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate, finely ground blast furnace gravity ash and bentonite;
[0008] The ultrafine high-titanium vanadium-titanium magnetite concentrate contains more than 90wt% of particles with a particle size of less than 0.074mm, the bentonite contains more than 95wt% of particles with a particle size of less than 0.074mm, and the finely ground blast furnace gravity ash contains more than 70wt% of particles with a particle size of less than 0.074mm.
[0009] b) The green balls are dried, preheated and roasted in sequence to obtain vanadium-titanium pellets.
[0010] Preferably, in step a), the carbon content of the finely ground blast furnace gravity ash is ≥ 20wt%.
[0011] Preferably, in step a), the bentonite content in the first mixture is 1-2wt%; the finely ground blast furnace gravity ash content in the second mixture is 0.1-10wt%, and the bentonite content is 1-2wt%.
[0012] Preferably, in step a), the particle size of the core of the green ball is 4-8 mm; the particle size of the green ball is 8-16 mm.
[0013] Preferably, step a) specifically comprises:
[0014] The first mixed material is put into a disc ball making machine, and a mother ball is first made by a water dripping mode, and then the first mixed material is adhered to the surface of the mother ball while spraying mist water to continue making balls, so as to obtain a raw ball core;
[0015] Subsequently, the second mixture is coated on the surface of the green ball core by spraying mist water while adhering the second mixture on the surface of the green ball core to obtain green balls.
[0016] Preferably, the rotation speed of the disc pelletizing machine is 20-25 r / min, and the inclination angle is 45-50°.
[0017] Preferably, in step a), the moisture content of the green balls is 7.5-8.5 wt%.
[0018] Preferably, in step b), the drying temperature is 120-170° C.; and the drying time is 1-3 hours.
[0019] Preferably, in step b), the preheating temperature is 800-850° C.; and the preheating time is 10-12 min.
[0020] Preferably, in step b), the calcination temperature is 1200-1300° C. and the calcination time is 10-15 min.
[0021] Compared with the prior art, the present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps: a) pelletizing a first mixture to obtain a green ball core; then coating the surface of the green ball core with a second mixture to obtain a green ball; the first mixture is a mixture of ultrafine-grained high-titanium vanadium-titanium magnetite concentrate and bentonite, and the second mixture is a mixture of ultrafine-grained high-titanium vanadium-titanium magnetite concentrate, finely ground blast furnace gravity ash and bentonite; the proportion of particles with a particle size of less than 0.074 mm in the ultrafine-grained high-titanium vanadium-titanium magnetite concentrate is more than 90wt%, the proportion of particles with a particle size of less than 0.074 mm in the bentonite is more than 95wt%, and the proportion of particles with a particle size of less than 0.074 mm in the finely ground blast furnace gravity ash is more than 70wt%; b) the green balls are dried, preheated and roasted in sequence to obtain vanadium-titanium pellets. The present invention forms different material structure patterns inside and outside the pellets by means of two-time pelletizing, and the fixed carbon of the blast furnace gravity ash added outside can be burned during the preheating process. The combustion not only produces CO2 gas, but also forms pore channels, which is conducive to the preheating of oxygen into the interior of the pellets, ensuring uniform oxidation inside and outside, and also provides sufficient heat guarantee for the oxidation crystallization of high-titanium vanadium-titanium magnetite. The preparation method provided by the present invention solves the occurrence of concentric cracks in vanadium-titanium pellets, improves the compressive strength of pellets, and recycles the solid waste resources of ironmaking plants, and has good promotion prospects. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] The present invention provides a method for preparing vanadium-titanium pellets, comprising the following steps:
[0024] a) pelletizing the first mixed material to obtain a green ball core; and then coating the surface of the green ball core with the second mixed material to obtain a green ball;
[0025] The first mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate and bentonite, and the second mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate, finely ground blast furnace gravity ash and bentonite;
[0026] b) The green balls are dried, preheated and roasted in sequence to obtain vanadium-titanium pellets.
[0027] In the preparation method provided by the present invention, in step a), the proportion of particles with a particle size of less than 0.074 mm in the ultrafine-grained high-titanium vanadium-titanium magnetite concentrate is more than 90wt%, preferably more than 94wt%; the TFe content of the ultrafine-grained high-titanium vanadium-titanium magnetite concentrate is preferably 55-56.5wt%, the FeO content is preferably ≥29wt%, the SiO2 content is preferably 3.3-3.5wt%, the TiO2 content is preferably 11-11.5wt%, and the V2O5 content is preferably 0.6-0.65wt%.
[0028] In the preparation method provided by the present invention, in step a), the proportion of particles with a particle size of less than 0.074 mm in the bentonite is more than 95wt%, preferably more than 99wt%; the CaO content of the bentonite is preferably 2-5wt%, the SiO2 content is preferably 40-60wt%, the Al2O3 content is preferably 12-18wt%, and the MgO content is preferably 2-5wt%.
[0029] In the preparation method provided by the present invention, in step a), the particles with a particle size of less than 0.074 mm in the finely ground blast furnace gravity ash account for more than 70wt%; the TFe content of the finely ground blast furnace gravity ash is preferably 35-40wt%, the CaO content is preferably 8-8.5wt%, the SiO2 content is preferably 6.5-7.5wt%, the TiO2 content is preferably 3-5wt%, and the C content is preferably ≥20wt%, more preferably 21-25wt%.
[0030] In the preparation method provided by the present invention, in step a), the bentonite content in the first mixture is preferably 1-2wt%, specifically 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%.
[0031] In the preparation method provided by the present invention, in step a), the content of finely ground blast furnace gravity ash in the second mixture is preferably 0.1-10wt%, specifically 0.1wt%, 0.5wt%, 1wt%, 3wt%, 5wt%, 7wt% or 10wt%; the content of bentonite in the second mixture is preferably 1-2wt%, specifically 1wt%, 1.2wt%, 1.5wt%, 1.7wt% or 2wt%.
[0032] In the preparation method provided by the present invention, in step a), the particle size of the inner core of the green ball is preferably 4-8 mm, specifically 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm or 8 mm; the particle size of the green ball is preferably 8-16 mm, specifically 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm or 16 mm.
[0033] In the preparation method provided by the present invention, the specific pelletizing process of step a) preferably includes:
[0034] The first mixed material is put into a disc ball making machine, and a mother ball is first made by a water dripping mode, and then the first mixed material is adhered to the surface of the mother ball while spraying mist water to continue making balls, so as to obtain a raw ball core;
[0035] Subsequently, the second mixture is coated on the surface of the green ball core by spraying mist water while adhering the second mixture on the surface of the green ball core to obtain green balls.
[0036] In the preparation method provided by the present invention, in the above-mentioned specific ball-making process, the size of the disc ball-making machine is preferably Φ1000×350mm; the rotation speed of the disc ball-making machine is preferably 20-25r / min, specifically 20r / min, 21r / min, 22r / min, 23r / min, 24r / min or 25r / min; the inclination angle of the disc ball-making machine is preferably 45-50°, specifically 45°, 46°, 47°, 48°, 49° or 50°.
[0037] In the preparation method provided by the present invention, in the above-mentioned specific ball-making process, the water content of the core of the green ball is preferably 7.5-8.5wt%; the water content of the green ball is preferably 7.5-8.5wt%.
[0038] In the preparation method provided by the present invention, in step b), the drying temperature is preferably 120-170°C, specifically 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C or 170°C; the drying time is preferably 1-3h, specifically 1h, 1.2h, 1.5h, 1.7h, 2h, 2.3h, 2.5h, 2.7h or 3h.
[0039] In the preparation method provided by the present invention, in step b), the preheating temperature is preferably 800-850°C, specifically 800°C, 805°C, 810°C, 815°C, 820°C, 825°C, 830°C, 835°C, 840°C, 845°C or 850°C; the preheating time is preferably 10-12 min, specifically 10 min, 10.5 min, 11 min, 11.5 min or 12 min.
[0040] In the preparation method provided by the present invention, in step b), the calcination temperature is preferably 1200-1300°C, specifically 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C or 1300°C; the calcination time is preferably 10-15min, specifically 10min, 10.5min, 11min, 11.5min, 12min, 12.5min, 13min, 13.5min, 14min, 14.5min or 15min.
[0041] In the preparation method provided by the present invention, in step b), after the calcination, the calcined product is cooled, and the cooling method is preferably natural cooling.
[0042] The preparation method provided by the present invention can ensure that the pellets produced from fine-grained high-titanium vanadium-titanium magnetite can form good pore channels during preheating and roasting, ensure uniform oxidation during preheating and roasting, improve the compressive strength of the pellets, stabilize the blast furnace raw material conditions, and strengthen blast furnace smelting. More specifically, the preparation method provided by the present invention has the following beneficial effects:
[0043] (1) By using two rounds of pelletizing, a double-layer vanadium-titanium pellet is formed, but the chemical composition and metallurgical properties of the pellets do not change much. After the blast furnace is used, the current sintering system is guaranteed not to change;
[0044] (2) The fixed carbon resources of the blast furnace gravity ash outside the vanadium-titanium pellets are utilized to form CO2 pore channels during the preheating process, which reduces the formation of Fe2O3 oxide layers in the vanadium-titanium pellets, promotes the uniformity of oxidation inside and outside the pellets, improves the occurrence of concentric cracks, and improves the compressive strength of the vanadium-titanium pellets;
[0045] (3) It not only recycles secondary resources in the iron-making process, but also provides sufficient heat for the vanadium-titanium pellets with a high content of high-melting-point phases, thereby promoting the oxidation crystallization effect of the vanadium-titanium pellets.
[0046] For the purpose of greater clarity, the present invention is described in detail with reference to the following examples and comparative examples.
[0047] In the following examples and comparative examples of the present invention, the physical and chemical parameters of the ultrafine vanadium-titanium concentrate, bentonite and blast furnace gravity ash used are shown in Table 1:
[0048] Table 1 Particle size distribution of materials used (wt%)
[0049] >0.15mm 0.15~0.074mm 0.074~0.044mm <0.074mm Vanadium Titanium Concentrate 0.53 4.65 27.70 94.82 Bentonite 99.71 Gravity ash (before fine grinding) 33.87 40.27 13.20 25.86 Gravity ash (finely ground) 1.21 27.74 35.21 71.05
[0050] In Table 1, the chemical composition indicators of the materials used are as follows:
[0051] Vanadium-titanium concentrate: w(TFe) 55.00-56.50%, w(FeO)>29%, w(SiO2) 3.30-3.50%, w(TiO2) 11.00-11.50%, w(V2O5) 0.60-0.65%;
[0052] Bentonite: w(CaO)2.00~5.00%, w(SiO2)40.00~60.00%, w(Al2O3)12.00~18.00%, w(MgO)2.00~5.00%;
[0053] Gravity ash: w(TFe)35.00~40.00%, w(CaO)8.00~8.50%, w(SiO2)6.50~7.50%, w(TiO2)3.00~5.00%, w(C)21.00~25.00%.
[0054] In the following embodiments and comparative examples of the present invention, the raw material ratios of vanadium-titanium pellets are shown in Table 2:
[0055] Table 2 Raw material ratio of high manganese concentrate pellets (wt%)
[0056]
[0057] Example 1
[0058] According to the ratio shown in Table 2, the vanadium-titanium concentrate and gravity ash are first placed in an oven for drying, the temperature is set to 150°C, and the drying time is 2 hours. Then, the vanadium-titanium concentrate and the corresponding proportion of bentonite are respectively added to a high-power mixer for thorough mixing for 10 minutes to form a mixture 1; the vanadium-titanium concentrate, the corresponding proportion of gravity ash and bentonite are added to a mixer for thorough mixing for 10 minutes to form a mixture 2.
[0059] Then, the mixture 1 and the mixture 2 are successively added to the disc ball making machine for ball making, the disc ball making machine is Φ1000×350mm, the rotation speed is 20r / min, the inclination angle is 48 degrees, and the water content of the balls is controlled to be 7.5-8.5wt%. Specifically, the mixture 1 is first added to the disc ball making machine for primary ball making, and the mother ball is first made by the mode of dripping water to form balls, and then the mode of spraying mist water while adhering the mixture 1 on the surface of the mother ball is changed to continue ball making, so as to obtain the raw ball core with a particle size of 4-8mm; then, the mixture 2 is added to the disc ball making machine for secondary ball making, and the mixture 2 is wrapped on the surface of the raw ball core by the mode of spraying mist water while adhering the mixture 2 on the surface of the raw ball core, so as to form raw balls with a particle size of 8-16mm. After the green balls are obtained, the falling strength and compressive strength of the green balls are tested. The falling strength test method is to raise the green balls to a height of 0.5M, and then let them fall freely onto an iron plate, and count the number of times the green balls are broken as the number of falls. The compressive strength test method is to directly put the green balls into the compression equipment for testing.
[0060] Finally, the qualified green balls are dried, preheated and roasted. The drying, preheating and roasting system is as follows: drying temperature 150℃, drying time 2 hours, preheating time 800℃, preheating time 10min, roasting temperature 1250℃, roasting time 15min; after roasting, take out and cool naturally to obtain vanadium-titanium pellets. After the vanadium-titanium pellets are obtained, the compressive strength and microscopic phase structure of the vanadium-titanium pellets are tested.
[0061] In this embodiment, the first ball making is 10 minutes, the second ball making is 10 minutes, the compressive strength of the green balls is 10.47N / piece, the drop strength is 4.6 times / piece, the moisture content of the green balls is 7.77wt%, and the bursting temperature is greater than 600°C; the compressive strength of the finished pellets is 2244N / piece, the TFe content is 54.88wt%, the SiO2 content is 4.05wt%, the CaO content is 0.51wt%, the Al2O3 content is 3.53wt%, the TiO2 content is 9.83wt%, the internal porosity is 31.42%, the pellet reduction degree is 68.16%, and the hematite mineral phase composition reaches 94.76%.
[0062] Example 2
[0063] The preparation process is similar to that of Example 1, except that the ratio of raw materials is different.
[0064] In this embodiment, the first ball making is 10 minutes, the second ball making is 10 minutes, the compressive strength of the green balls is 10.07N / piece, the drop strength is 4.5 times / piece, the moisture content of the green balls is 7.58wt%, and the bursting temperature is greater than 600°C; the compressive strength of the finished pellets is 2510N / piece, the TFe content is 54.90wt%, the SiO2 content is 4.10wt%, the CaO content is 0.65wt%, the Al2O3 content is 3.53wt%, the TiO2 content is 9.71wt%, the internal porosity is 34.79%, the pellet ore reduction degree is 70.06%, and the hematite mineral phase composition reaches 94.55%.
[0065] Comparative Example 1
[0066] The preparation process is similar to that of Example 1, except that the raw material ratio is different and pelletizing is performed only once.
[0067] The ball making process takes 20 minutes at a time, and the compressive strength of the green balls is 10.68N / piece, the drop strength is 4.7 times / piece, the moisture content of the green balls is 8.04%, and the bursting temperature is greater than 600℃; the compressive strength of the finished pellets is 1925N / piece, the TFe content is 54.75wt%, the SiO2 content is 3.94wt%, the CaO content is 0.32wt%, the Al2O3 content is 3.48wt%, the TiO2 content is 9.90wt%, the internal porosity is 28.55%, the pellet ore reduction degree is 67.24%, and the hematite mineral phase composition reaches 94.32%.
[0068] It can be seen from the above embodiments and comparative examples that, with the further increase of the blast furnace gravity ash ratio, the green ball drop strength and compressive strength show a certain quality decline, but the compressive strength of the finished pellets is greatly improved, and the internal porosity of the pellets is gradually increased, and the reduction degree is gradually optimized. Therefore, it is shown that the addition of gravity ash to the vanadium-titanium pellets can improve the Fe2O3 dense oxide layer structure formed by the rapid oxidation of Fe3O4 in the ultra-fine vanadium-titanium concentrate, thereby reducing the occurrence of concentric cracks and improving the compressive strength of the pellets.
[0069] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing vanadium-titanium pellets, characterized in that: The following steps are involved: a) pelletizing the first mixed material to obtain a green ball core; and then coating the surface of the green ball core with the second mixed material to obtain a green ball; The first mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate and bentonite, and the second mixed material is a mixture of ultrafine high-titanium vanadium-titanium magnetite concentrate, finely ground blast furnace gravity ash and bentonite; The ultrafine high-titanium vanadium-titanium magnetite concentrate contains more than 90wt% of particles with a particle size of less than 0.074mm, the bentonite contains more than 95wt% of particles with a particle size of less than 0.074mm, and the finely ground blast furnace gravity ash contains more than 70wt% of particles with a particle size of less than 0.074mm. b) The green balls are dried, preheated and roasted in sequence to obtain vanadium-titanium pellets.
2. The preparation method according to claim 1, characterized in that: In step a), the carbon content of the finely ground blast furnace gravity ash is ≥ 20wt%.
3. The preparation method according to claim 1, characterized in that: In step a), the bentonite content in the first mixture is 1-2wt%; the finely ground blast furnace gravity ash content in the second mixture is 0.1-10wt%, and the bentonite content is 1-2wt%.
4. The preparation method according to claim 1, characterized in that: In step a), the particle size of the core of the green ball is 4 to 8 mm; the particle size of the green ball is 8 to 16 mm.
5. The preparation method according to claim 1, characterized in that: Step a) specifically includes: The first mixed material is put into a disc ball making machine, and a mother ball is first made by a water dripping mode, and then the first mixed material is adhered to the surface of the mother ball while spraying mist water to continue making balls, so as to obtain a raw ball core; Subsequently, the second mixture is coated on the surface of the green ball core by spraying mist water while adhering the second mixture on the surface of the green ball core to obtain green balls.
6. The preparation method according to claim 5, characterized in that: The rotation speed of the disc pelletizing machine is 20-25 r / min, and the inclination angle is 45-50°.
7. The preparation method according to claim 1, characterized in that: In step a), the water content of the green balls is 7.5-8.5 wt%.
8. The preparation method according to claim 1, characterized in that: In step b), the drying temperature is 120-170° C. and the drying time is 1-3 hours.
9. The preparation method according to claim 1, characterized in that: In step b), the preheating temperature is 800-850° C.; the preheating time is 10-12 minutes.
10. The preparation method according to claim 1, characterized in that: In step b), the calcination temperature is 1200-1300° C. and the calcination time is 10-15 minutes.
Citation Information
Cited By
Two-stage variable-rotating-speed pelletizing method of iron ore pellets for low-carbon ironmaking
CN120060634A